Analisis Penerapan ISAK 35 Tentang Laporan Keuangan Organisasi Nonlaba pada Gereja HKBP Kutabumi - Ruth Gabirella Apriliana; Ulupui, I Gusti Ketut Agung; Pahala, Indra (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This research aims to apply ISAK 35 guidelines in preparing the financial statements of HKBP Kutabumi Church for the year 2022, following the accounting cycle process. The research method used is descriptive qualitative analysis. Data collection techniques include interviews, documentation, and observation. The data sources utilized are primary and secondary data. The results of this study indicate that HKBP Kutabumi Church has not yet implemented financial reporting based on ISAK 35. The church's financial statements are prepared on a cash basis with a single entry recording system, where only cash inflows and outflows are recorded. Additionally, church officials have not conducted an inventory of assets owned. Therefore, the researcher compiled and prepared the financial statements of HKBP Kutabumi Church for the year 2022 in accordance with ISAK 35 accounting standards. These include the statement of financial position, statement of comprehensive income, statement of changes in net assets, statement of cash flows, and notes to the financial statements.